1997
DOI: 10.1046/j.1365-2559.1997.d01-604.x
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic cancer involving pancreatic duct epithelium and its mimicry of primary pancreatic cancer

Abstract: We investigated 47 autopsy cases of metastatic cancer involving the pancreas. Metastatic disease in nine cases involved the pancreatic duct epithelium. In two cases, metastatic cancer cells showed Pagetoid features. In three cases, pancreatic metastatic disease showed solitary proliferation with focal in situ carcinoma-like lesions mimicking primary pancreatic cancers. Each of these three cases had primary lung adenocarcinomas. Serial sections revealed abrupt borders between the in situ carcinoma-like lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
7
1
Order By: Relevance
“…All of their three cases were primary lung adenocarcinomas. 12 However, we did not identify such cases in the present study.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…All of their three cases were primary lung adenocarcinomas. 12 However, we did not identify such cases in the present study.…”
Section: Discussioncontrasting
confidence: 59%
“…Matsukuma et al recently described a unique case of pancreatic metastasis: intraductal pagetoid spread of metastatic cancer cells. All of their three cases were primary lung adenocarcinomas 12 . However, we did not identify such cases in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…We also observed colonization of the ductal epithelium by metastatic tumor cells in some of our cases. Both intraductal growth and pagetoid spread to the ducts have been reported in the literature as well [53]. Fat necrosis and other signs of pancreatic injury may be seen [63].…”
Section: Discussionmentioning
confidence: 92%
“…While the majority of the tumors involving the pancreas are either of pancreatic, biliary, or periampullary origin, there are a variety of tumors involving this organ secondarily, which have different clinicopathological presentations and outcomes [10,11,20,26,32,39,45,46,53,63,66,67,75,77,96]. Most of the studies reported in the literature focus on the radiological and ultrasonographic characteristics of secondary tumors and their differential diagnosis from primary pancreatic carcinomas [10,11,20,26,39,66,67,77,96].…”
Section: Introductionmentioning
confidence: 99%
“…The most common site can be lung carcinoma, renal cell carcinoma, colon carcinoma, or stomach carcinoma 913,15,16,18,19,2127. Mesa et al reviewed all secondary tumours of pancreas in literature by Medline between 1966 and 2003 18.…”
Section: Frequency Of Pancreatic Metastasismentioning
confidence: 99%